Criminal liability for interfering with the legal professional activities of journalists (art. 171 of the Criminal Code): a scientific and practical comment - Movchan R.; Hel A. (Науково-інформаційний вісник Івано-Франківського університету права імені Короля Данила Галицького)
Purpose. Scientific and practical commentary on certain provisions of Art. 171 of the Criminal Code of Ukraine. In order to achieve the declared goal, an appropriate methodology was chosen, in particular, philosophical, general scientific and specifically scientific methods were used. Based on the results of writing the article, firstly, recommendations were formulated for solving those debatable issues, the lack of answers to which can prevent effective law enforcement of Art. 171 of the Criminal Code of Ukraine, secondly, the shortcomings inherent in the corresponding norm were identified, the presence of which already negatively affects its effectiveness, and proposals were made for their elimination. The scientific novelty lies in the fact that new recommendations on qualifications and proposals for improving certain provisions of Art. 171 of the Criminal Code of Ukraine. In particular, it was proven that cases of mental or physical pressure on the journalist’s close relatives should not be qualified under Art. 171, and according to Art. 345-1 of the Criminal Code of Ukraine. Additional arguments are presented in favor of the fact that instead of enumerating the forms of obstruction to the legal professional activity of a journalist in the analyzed criminal law norm, it would be appropriate to point to the single generalizing term “obstruction”, which, among other things, included the concept of “influence”. Recommendations for distinguishing the investigated criminal offense from criminal offenses against life and health have been developed. The proposal of the researchers to present Part 3 of Art. 171 of the Criminal Code of Ukraine in the following wording: “Actions provided for in part 1 or part 2 of this article, if they were committed by an official using his official position or with the prior conspiracy of a group of persons”. Practical significance. Formulated conclusions can be used in rule-making, law enforcement and scientific activities.